Análisis situacional y propuesta de un plan financiero de las pequeñas empresas familiares del cantón Valencia, Año 2011. - Vizuele Segovia, María Lourdes (2013)
This research was conducted with the purpose of improving the administration and organization of small family businesses Canton Valencia, in order to improve their operability through the use of financial plans to be clear profits while increasing them and improve quality of life for its owners, growing as a company, providing employment opportunities and providing a high degree of importancetothesocietyinwhichtheyareestablished. Obtaining information is performed by applying surveys to owners as the internal and external customers as a means of small family businesses Canton Valencia. The owners survey consisted of 20 questions and the customer survey to supplement for 5 questions, also worth mentioning that in terms of research methods used deductive and inductive and financier who served very helpful for gathering data, and observational techniques, surveys and interviews. The situational analysis conducted on small family businesses Canton Valencia showed the absence of some important elements such as vision, mission, organizational structure, corporate values and corporate policies. He cleared the importance of financial planning in a company, making known the financial statements that conform with the reasons and financial indicators we tested positiveforimplementingthisproject. A proposal was designed starting with situational analysis (SWOT) and then financial plan that originated it after checking and negation of hypotheses allowed us to conclude that while variables that will surely recommend owners of small family businesses Valencia county disregarded in a new year of operations.